PEDAGOGICAL SUPPORT OF FORMATION OF MORAL AWARENESS OF STUDENTS - Aksana F. Hodko (Russian State Vocational Pedagogical University, 2015)
The purpose of this article is to consider the features of pedagogical support of the formation of moral awareness of students, its main components and principles, to describe the components of the professional culture of the teacher, to determine the pedagogical conditions of development of moral awareness of students on the basis of the realization of the principle of the educative training of modern specialists.Methods. Methods involve comparative analysis of literary sources, analysis of documents, systematization and generalization of theoretical material, logicaland-historical analysis, causal analysis, functional analysis, system-andstructural analysis.Results. It is shown that the global goal of modern high school is the formation of a constructive, creative personality, embodying a highly qualified specialist, a good family man, a conscious citizen and patriot of his/her homeland, responsible for its present and future. The importance of ideological and educational functions of the teacher significantly increases and is aimed at updating the ideological position of student, his professional, civic, and spiritual-and-moral formation. Moral development of personality is a process of the formation and changing of the individual as the subject of morality, involving the development of individual systems of moral values on the basis of the adoption of moral experience of mankind, which is the evidence of moral self-affirmation and personal integrity. Modern social-and-cultural conditions require updating the content, forms and methods of education in an establishment of higher education with the reorientation from the traditional educational work to personal-oriented educational process based on the use of active (interactive) pedagogical tools. An important requirement for effective organization of educational process of students is the realization of proved organizational and psycho-pedagogical conditions. Wellorganized process of education is an integral element of the education of the person as a whole and it contributes to the choice of the person's own life and development. The effectiveness of educational work depends largely on the level of preparedness of a pedagogue to a realization of the goals and objectives of education, possession of modern educational technologies of psycho-and-pedagogical interaction in the social-and-cultural educational environment, personal development in the conditions of information society.Scientific novelty. The paper gives valuable information on the concrete definition and systematization of the features of pedagogical support of the formation of moral awareness of students.Practical significance. Research materials can be used in the practice of curators, teachers, employees of the Department of ideological and educational work, workers, psycho-and-pedagogical service for the identification and correction of value orientations of the individual, for the creating the best conditions for their self-development and self-realization, for the creation of a favorable educational environment at the establishment of higher education.